2012
DOI: 10.1007/s11160-012-9252-z
|View full text |Cite
|
Sign up to set email alerts
|

Global in scope and regionally rich: an IndiSeas workshop helps shape the future of marine ecosystem indicators

Abstract: This report summarizes the outcomes of an IndiSeas workshop aimed at using ecosystem indicators to evaluate the status of the world's exploited marine ecosystems in support of an ecosystem approach to fisheries, and global policy drivers such as the 2020 targets of the Convention on Biological Diversity. Key issues covered relate to the selection and integration of multi-disciplinary indicators, including climate, biodiversity and human dimension indicators, and to the development of dataand model-based method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…There are examples from other regions of how models such as Ecopath with Ecosim are used to evaluate TACs across multiple species by being utilized as management strategy evaluation tools (Grüss et al, 2016 and references therein). There are also other advances in food web models for marine systems for guiding fisheries management (Smith et al, 2011(Smith et al, , 2015Shin et al, 2012). Our work adds on to these efforts by proposing TAC values until 2020 based on an integrated circulation-biogeochemical model that includes the effect of environmental and climate variations.…”
Section: Discussionmentioning
confidence: 99%
“…There are examples from other regions of how models such as Ecopath with Ecosim are used to evaluate TACs across multiple species by being utilized as management strategy evaluation tools (Grüss et al, 2016 and references therein). There are also other advances in food web models for marine systems for guiding fisheries management (Smith et al, 2011(Smith et al, , 2015Shin et al, 2012). Our work adds on to these efforts by proposing TAC values until 2020 based on an integrated circulation-biogeochemical model that includes the effect of environmental and climate variations.…”
Section: Discussionmentioning
confidence: 99%
“…indiseas. org) is underway (Shin et al 2012). Further, development of reference levels for the indicators selected from this study is seen as a research priority for the future.…”
Section: A Step-wise Process To Examine Changes In the Southern Bengumentioning
confidence: 97%
“…The averaging approach is the most commonly used method to aggregate indicators (Shin et al, 2012) and consists of simple calculations, using methods such as arithmetic average, hierarchical average, weighted average, median, sum, product or combinations of those rules, to come up with an overall assessment value. Ojaveer and Eero (2011) showed that in cases where a large number of indicators is available, the choice of e.g., either medians or averages in aggregating indicators did not substantially influence the assessment results.…”
Section: Averaging Approachmentioning
confidence: 99%
“…However, interpretation is less intuitive than other methods, as information on individual indicators in each ecosystem is lost (Shin et al, 2012) and links to management options are less obvious.…”
Section: Multidimensional Approachesmentioning
confidence: 99%